PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016 - -, Muhammad Supredi (EKONOMIA, 2018)
The Effect of Liquidity and Solvency on the value of the company in the food and beverage sub-sector company listed on the Indonesia Stock Exchange. (under Guidance of Supervisor 1 Mr. LCA Robin Jonathan and 2nd Supervisor Mrs. Ivana Nina Esterlin Barus).Commodity companies manufacturing food and beverage sub-sectors tend to experience a decline in performance in recent years will reduce the value of the company. The company's value is influenced by several factors, one of which is the company's financial performance.This study aims to determine the effect of: 1) Current Ratio on Company Value; 2) Debt To Equity Ratio to Company Value. The data used in this study are secondary data in the form of financial statements for 2013-2016 obtained from the official website of the Indonesia Stock Exchange, www.idx.co.id.The method used in this research is descriptive method. Of the 15 population companies listed on the Indonesia Stock Exchange, there were 12 samples of companies that met the testing criteria. So that the amount of data to be analyzed is 48. Before carrying out the data analysis technique, the first classical assumption is carried out. Hypothesis testing using multiple linear regression test by conducting t test and F test with the help of SPSS software.The results of the study concluded that H1 was rejected because Current Ratio had no significant positive effect on firm value. H2 received by Debt To Equty Ratio has a significant positive effect on the value of the company. H3 was rejected because. H3 Current Ratio and Debt To Equty Ratio are accepted because they have a significant positive influence together on the value of the compan